Development and Validation of the Simple and Sensitive Spectrophotometric Method of Amoxicillin Determination in Tablets using Sulphanilamides - Oksana Kostiv; Olha Korkuna; Petro Rydchuk (Acta Chimica Slovenica, 2020)
A rapid, simple and sensitive spectrophotometric method for the determination of amoxicillin (AM) is described. The method is based on the previous sulphanilamide (SA) and sulphathiazole (STZ) diazotization in the medium of 0.6–0.7 M hydrochloric acid and their subsequent interaction with amoxicillin at pH = 10.5 with formation of yellow-colored azo compouds. Effective molar absorptivities at the absorbance maxima at 445 nm (SA) and 448 nm (STZ) for azo compounds were (1.74 ± 0,06)∙104 L×mol-1×cm-1  and (1.97 ± 0,05)∙104 L×mol-1×cm-1, respectively. Stoichiometric ratios of the components of azo compounds were determined using continuous variations method. Based on the optimum reaction conditions, new methods were developed. These methods allow to determine the amoxicillin in concentration range 1.3–32.9 mg×mL-1 with sulphanilamide and 0.7–27.4 mg×mL-1 with sulphathiazole. The methods were successfully validated for amoxicillin determination in tablets “Amoxil”.